Komunikasi Bisnis Berkeadilan Gender di Perusahaan BUMN - Aida Maslamah; Sa’diyah El Adawiyah (LPPM Stikosa - AWS, 2026)
In Indonesia, corporate leadership positions are predominantly held by men, accounting for 69.37%, compared to 30.63% occupied by women (BPS, 2020). This study examines the experiences of a female leader in a state-owned enterprise (SOE) who has struggled to overcome glass ceiling barriers and develop gender-equitable communication throughout her career.This research employs a qualitative approach, using a case study method to model the communicator role of a female corporate director in an SOE. Data collection methods include observations, in-depth interviews, and document analysis. The analysis and presentation of findings are guided by two theoretical frameworks: Tubbs and Moss’s Communication Style Theory and Marilyn Loden’s Gender Communication and Glass Ceiling Theory. This study examines the glass ceiling barriers experienced by Lies Permana Lestari in her career within a state-owned enterprise (SOE). Findings indicate three major obstacles: gender-biased promotion discrimination, stereotypes that women are unfit to lead in the male-dominated transportation sector, and communication challenges linked to domestic roles. These barriers highlight how SOE business communication practices remain shaped by masculine norms that constrain gender equality. To address these challenges, Lies employed dynamic and egalitarian communication styles. These approaches proved effective not only for her personal advancement but also for transforming organizational communication patterns. Specifically, she encouraged participatory meetings, facilitated equal dialogue between male and female employees, and prioritized collaboration over rigid hierarchy. By doing so, Lies not only overcame the glass ceiling but also contributed to fostering a more gender-equitable communication culture in the SOE. This case underscores the potential of communication strategies to challenge structural and cultural barriers in organizational settings.